Problem Lokalitas dalam Bisnis Radio Network - - Rahayu (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
The emergence of radio network has some consequencies. These relate to the ownership of the network, problems of locality and threads to democracy. Some may view that the networks have strengthened the position of radio. The others believe that the netwrok risks the local power in Indonesia. This article explores the problems of the radio networks in Indonesia, especially when dealing with the local elements.